Understanding socio-economic aspects of adoption and effects of Climate Smart Agricultural (CSA) practices in Guatemala - Howland, Fanny C.; Arora, Diksha; Bonilla Findji, Osana; Andrieu, Nadine (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2019)
Using a case study of a Climate-Smart Village (CSV) in Guatemala, this study presents an integrated methodological framework to better understand the adoption of Climate Smart Agricultural (CSA) practices, gender-disaggregated motivations, and constraints in smallholder farming communities. It uses a mixed-method approach, using quantitative data gathered thought the ICT based CSV Monitoring Plan and complement and qualitative data from focus group discussions with men and women farmers as well as semi-structured interviews.